Effects of Ag addition on some physical properties of granular YBa2Cu3O7-δ superconductor - Azambuja,Paula de (2009)
The effects of Ag addition on some physical properties of YBa2Cu3O7-δ superconductor has been studied. The samples were produced by different routes and characterized by scanning electron microscopy, differential thermal analysis, thermogravimetric analysis, X-ray diffraction and nanoindentation. The superconducting properties were studied by dc magnetization and electrical resistivity measurements. The X-ray patterns revealed that all samples were polycrystalline and corresponded to the orthorhombic YBa2Cu3O7-δ phase. However, for some samples, silver appears to be present within the grains. The superconducting properties were not significantly influenced by Ag addition. Hardness and elastic modulus were also obtained by instrumented indentation. Ag addition was found to be effective in improving the mechanical properties, probably by filling the pores in the grain boundaries. Hardness profiles indicated values between 3.1 and 3.4 GPa at deep tip penetration depths. The highest elastic modulus of 146 GPa was attained for samples prepared using Y2O3, BaCO3, CuO and Ag2O as precursors, while the lowest modulus (125 GPa) was obtained for the pure YBa2Cu3O7-δ sample.